Dissolution Kinetics and Thermodynamics of Thiourea in Triethylene Glycol + Water Mixtures - Li, Hua; Chen, Xiaoshuang; Guo, Feng (Asian Journal of Chemistry, 2010)
Isopropyl mercaptan is an important pharmaceutical intermediate and chemical material. The dissolution of thiourea in solvents is very important for the production of isopropyl mercaptan. The aims of this study are to examine the dissolution kinetics and thermodynamics of thiourea in solvents at 297.15, 307.65, 317.05 and 332.85 K in the mass fraction of triethylene glycol being 0.63 and to present an alternative process for producing isopropyl mercaptan. In order to investigate the dissolution kinetics and thermodynamics of thiourea in triethylene glycol solution, the concentrations of solution, reaction temperature were selected as experimental parameters. It was determined that the dissolution rate of thiourea increased with increasing solution concentration and temperature. An empirical equation was used in fitting the data. The activation energy and entropy change ΔSº of the process was found to be 38.4709 and 0.1070 kJ/mol, respectively.